Durkheim's "Suicide" in the Zombie Apocalypse. (May 2017) - Mueller, Anna S.; Abrutyn, Seth; Osborne, Melissa
Hypothesizing the end of functional society by reading Durkheim and watching "The Walking Dead, " three scholars consider how low social integration and low moral regulation shape suicide risk at the group level.